THE ROLE OF THE FAMILY INSTITUTE IN EDUCATING A PROFESSIONAL GENERATION - Mirzaeva, Kamola (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
A calm environment is first of all necessary for the child to start the education of the youth in the right way and to start the education in good quality. A peaceful environment begins in the family, in a small homeland. There is no doubt that the perfect establishment of family institutions will serve as a foundation for the future of the state. This article discusses the role and importance of family institutions in the education of a well-rounded generation.